"So begins the demise of #Superman from Metropolis": Consumers' Twitter reactions to an athlete's transgression. Issue 5 (November 2020) - Sveinson, Katherine; Hoeber, Larena
Highlights: We explore an athlete transgression in the form of a homophobic slur. Twitter responses to the transgression are analyzed via critical discourse analysis. Language use by sport consumers in tweets creates both inclusivity and exclusivity. Managing transgressions becomes complicated in the age of political correctness. Abstract: When athlete transgressions occur both on and off the field, there can be negative impacts on stakeholders. Therefore, it is essential to explore how consumers react to transgressions to gain a better understanding of how they can be successfully managed. The purpose of this study was to explore consumers' Twitter reactions to an athlete's transgression using a homophobic slur, drawing on critical discourse studies as a conceptual framework. Using Visual Twitter Analytics (Vista), tweets were collected over the 2017 Toronto Blue Jays' season. For this study, the subset of tweets related to the incident were isolated. We found a duality in discourses, in that consumers shared perspectives for and against the use of homophobic language in sport. Practically, many consumers supported the idea of athletes being assigned a punishment for this type of language use. While consequences may satisfy some consumers, a cultural change within the organization and fan base is required to create an inclusive sport environment regarding language use.